Faktor Yang Memengaruhi Perilaku Pencegahan Diabetes Melitus Di Wilayah Kerja Puskesmas Pargarutan Kecamatan Angkola Timur Kabupaten Tapanuli Selatan - Reza Indra Rambe; Mappeaty Nyorong; Nur’aini Nur’aini (Pusat Riset dan Inovasi Nasional, 2023)
Diabetes mellitus (DM) is a disease in which glucose (simple sugar) levels in the blood are high because the body cannot release or use insulin adequately. Normal blood sugar levels in the morning after fasting the night before are 70-110 mg/dL of blood. Blood sugar levels are usually less than 120-140 mg/dL 2 hours after eating and drinking fluids containing sugar or other carbohydrates. The purpose of the study was to determine the factors that influence the behavior of preventing diabetes mellitus in the Work Area of ​​the Pargarutan Health Center, East Angkola District, South Tapanuli Regency. The research design used a quantitative method which was carried out by an analytical survey with a Cross Sectional Study approach. The population in this study were all patients with diabetes mellitus, as many as 321 patients. Samples using the Accidental Sampling system were 76 patients. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there was an effect of family history, support from health workers, physical activity, diet, family support and social culture on diabetes mellitus prevention behavior in the Work Area of ​​the Pargarutan Health Center, East Angkola District, South Tapanuli Regency. While the most dominant factor is diet. The conclusion of this study is that there is an influence of family history, support from health workers, physical activity, diet, family support and socio-culture on diabetes mellitus prevention behavior in the Pargarutan Health Center Work Area, East Angkola District, South Tapanuli Regency. It is recommended that the Pargarutan Health Center is expected to provide counseling about diabetes mellitus and carry out a diabetes mellitus control program to reduce the number of DM sufferers.